Bicarbonate Inhibits Bacterial Growth and Biofilm Formation of Prevalent Cystic Fibrosis Pathogens - Dobay, Orsolya; Laub, Krisztina; Stercz, Balázs; Kéri, Adrienn; Balázs, Bernadett; Tóthpál, Adrienn; Kardos, Szilvia; Jaikumpun, Pongsiri; Ruksakiet, Kasidid; Quinton, Paul M.; Zsembery, Ákos (Frontiers in Microbiology, 2018)
We investigated the effects of bicarbonate on the growth of several different bacteria as well as its effects on biofilm formation and intracellular cAMP concentration in Pseudomonas aeruginosa. Biofilm formation was examined in 96-well plates, with or without bicarbonate. The cAMP production of bacteria was measured by a commercial assay kit. We found that NaHCO3 (100 mmol l-1) significantly inhibited, whereas NaCl (100 mmol l-1) did not influence the growth of planktonic bacteria. MIC and MBC measurements indicated that the effect of HCO3- is bacteriostatic rather than bactericidal. Moreover, NaHCO3 prevented biofilm formation as a function of concentration. Bicarbonate and alkalinization of external pH induced a significant increase in intracellular cAMP levels. In conclusion, HCO3- impedes the planktonic growth of different bacteria and impedes biofilm formation by P. aeruginosa that is associated with increased intracellular cAMP production. These findings suggest that aerosol inhalation therapy with HCO3- solutions may help improve respiratory hygiene in patients with cystic fibrosis and possibly other chronically infected lung diseases.